Welded for Work: A Tracer Study on the Career Outcomes of Welding and Fabrication Technology Graduates of Batangas State University - Irish Giselle C. Bautista; Czarelle P. Lepran (Future Science / FSH-PH Publications, 2025)
This tracer study examined the career outcomes of Bachelor of Industrial Technology graduates majoring in Welding and Fabrication Technology (BIT-WFT) from Batangas State University for academic years 2021–2023. The study aimed to assess graduates’ demographic and educational profiles, employment outcomes, relevance of acquired competencies, and job satisfaction, with the end goal of proposing an action plan to improve employability. Data from 55 graduates revealed that most were male, aged 20–24, and had passed NC II and NC III certifications. The employment rate was 95%, with the majority securing jobs within 2–5 months after graduation, primarily in the non-government sector as pipe welders and fabricators. AG&P emerged as the leading employer, with typical monthly salaries ranging from ₱10,000 to ₱30,000. Respondents perceived their course, curriculum, and competencies as highly relevant to their employment, particularly problem-solving, critical thinking, and human relations skills. While most graduates expressed job satisfaction, salary and growth opportunities influenced their intent to stay or change jobs. The study concludes that the BIT-WFT program is generally effective in preparing graduates for industry needs but highlights areas for curriculum alignment, professional growth, and industry partnerships.